1976
DOI: 10.1016/s0031-9422(00)94419-4
|View full text |Cite
|
Sign up to set email alerts
|

Endosperm sterol phenotype and germination in wheat

Abstract: Abstract-Free and conjugated sterols of endosperm, coats, scutellum, coleoptile and roots have been analysed at different germination stages in two wheat cultivars with different endosperm sterol phenotypes. It seems that sterol metabolism of the developing tissues, namely coleoptile and roots, is not affected by the sterol conjugation profile of the endosperm. Enough sterol is present in the mature embryo to supply the germinating axis during the observation period (144 hr at 16°). The data suggest that stero… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

1977
1977
2005
2005

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…This difference was more pronounced when analyzing refined flour (endosperm), because the high content of palmitate provided by the D genome is expressed only in the endosperm. In fact, the fatty acids in FASE from other parts of the HW kernel always have a high linoleate content (45). GC-FID Analysis of FASE.…”
Section: Resultsmentioning
confidence: 99%
“…This difference was more pronounced when analyzing refined flour (endosperm), because the high content of palmitate provided by the D genome is expressed only in the endosperm. In fact, the fatty acids in FASE from other parts of the HW kernel always have a high linoleate content (45). GC-FID Analysis of FASE.…”
Section: Resultsmentioning
confidence: 99%
“…The predominant form varies, depending on plant and tissue: S is predominant in apple fruit mesocarp (3), SE is predominant in the endosperm of some wheat varieties (18), and ASG is predominant in potato tuber (4). The distribution of these sterols in plant tissues is mainly in the microsomal fraction and in the mitochondrial plus Golgi fraction (6,7).…”
mentioning
confidence: 99%
“…During germination and seedling development there is an increase in free sterol (Grunwald, 1 9 7 5~;Duperon, 1971;Kemp et al, 1967a;Geuns, 1973; which may in part result from hydrolysis of steryl ester reserves in the seed (Torres et al, 1976;Hughes & Goad, 1983). It seems that in some seeds the capacity of the endosperm or cotyledons for sterol synthesis is rather low or even absent during the initial stages of germination (Kemp et al, 19676;Baisted, 1971;Shrewry & Stobart 1974a;McKean & Nes, 1977).…”
Section: Sterol Synthesis During Seed Development Seed Germination Amentioning
confidence: 99%
“…During the early phase of embryo axis growth the sterol requirements for new membrane formation may be met by transfer of sterol from the seed store (Torres et al, 1976) although this could not be demonstrated in Pinuspinea seedlings (McKean & Nes, 1977). However, as the seedling axis develops it acquires the ability to synthesize sterol as revealed by the incorporation of [2-14C]mevalonic acid into sterol (Geuns, 1973;Shrewry & Stobart, 1974a;Fang & Baisted, 1975;McKean & Nes, 1977).…”
Section: Sterol Synthesis During Seed Development Seed Germination Amentioning
confidence: 99%